A Comparison of Chinese and UK Portfolios Using Value-at-Risk Approaches - ZHOU, Mengjia (2013)
With the continuous development of the Chinese Emerging financial market, numerous global investors have been paying great attention on this young market. The Chinese financial market holds its own characteristics, distinguishing from the developed financial market. Thus, by the stake of the investors, it is necessary to understand the Chinese financial risk and explore the effective risk management approaches. In the current field of quantitative risk management, Value-at-Risk is the most recognised and widely implemented methods among financial institutions, companies and private organisations. Abundant researchers have been evaluated the linear instruments but the limited works concern non-linear instruments. The objectives of this paper are two folds. First, it will invest a UK portfolio and one Chinese portfolio and collecting data from the real trading markets. Second, the two typical portfolios include linear instruments and non-linear instruments. The normal delta approach is not suitable because it may underestimate or overestimate the portfolio P/L. The Historical Simulation method, Monte-Carlo simulation method and Quadratic model approach are implemented for the risk estimation. Each method will be backtested to further verify its accuracy.